Adequacy of DEA as a regulatory tool in the water sector. The impact of data uncertainty. Issue 85 (July 2018) - Cabrera, E.; Estruch-Juan, E.; Molinos-Senante, M.
Highlights: Score of Data Envelopment Analysis is greatly affected by data quality. Water sector data quality may be insufficient for DEA use in regulation. Water services regulators should collect data quality information. Yardstick competition with DEA is very sensitive to data uncertainty. Abstract: The regulation of water services shares many similarities with that of other utilities such as electricity or telecommunications. As a result, similar methods are often used by regulators to assess the efficiency of companies in those sectors. Data Envelopment Analysis (DEA) is one of those widely applied methods. This paper aims to determine the adequacy of DEA as a regulatory tool for urban water services, with a special focus on the quality of the available data. In order to obtain useful conclusions, two DEA simulations were performed with audited data from 194 water utilities, officially made available by the Portuguese water regulatory authority (ERSAR). Both simulations will demonstrate that the inherent inaccuracies found in some of the key data provided by water utilities represent a significant obstacle to obtain meaningful results with the DEA technique. This could represent a paradigm shift for some of the regulatory authorities currently using DEA or similar techniques, as the complexity of the method does not seem to be justified by a better analysis of the comparative performance of the different services.